2006
DOI: 10.1111/j.1468-3083.2006.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine spiradenoma: co‐expression of cytokeratin and smooth muscle actin suggesting differentiation toward myoepithelial cells

Abstract: 121nipples. 2,5 Microscopically, it consists of mature sebaceous glands arranged in a band-like pattern in the upper dermis, independent of hair structures and lactiferous ducts. 6 Unilateral-located areolar sebaceous hyperplasia in a male patient has been reported previously only once, 7 so this is the second report of this rare entity. With regard to the origin of this disorder, some authors have proposed that areolar sebaceous hyperplasia in male subjects should be interpreted as a malformation rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…(e) K17 expression in hidroacanthoma simplex: K17, a keratin typical of activated and hyperproliferative keratinocytes, was strongly expressed in tumor cells of hidroacanthoma simplex, reported by Kurokawa et al (69) (with permission) (original magnification, × 100). (f) K17 expression in eccrine spiradenoma: K17, a keratin that also is characteristic of contractile myoepithelial cells, was intensely expressed in tumor cells (together with α‐smooth muscle‐type actin), suggesting that eccrine spiradenoma differentiates to myoepithelial cells, reported by Kurokawa et al (76) (with permission) (original magnification, × 100). (g) K10 expression in intraepidermal eccrine porocarcinoma: K10 is strongly expressed in the intraepidermal tumor cells, reported by Kurokawa et al (100) (with permission) (original magnification, × 40).…”
Section: Distribution and Significance Of Keratin Expression In Humanmentioning
confidence: 82%
See 1 more Smart Citation
“…(e) K17 expression in hidroacanthoma simplex: K17, a keratin typical of activated and hyperproliferative keratinocytes, was strongly expressed in tumor cells of hidroacanthoma simplex, reported by Kurokawa et al (69) (with permission) (original magnification, × 100). (f) K17 expression in eccrine spiradenoma: K17, a keratin that also is characteristic of contractile myoepithelial cells, was intensely expressed in tumor cells (together with α‐smooth muscle‐type actin), suggesting that eccrine spiradenoma differentiates to myoepithelial cells, reported by Kurokawa et al (76) (with permission) (original magnification, × 100). (g) K10 expression in intraepidermal eccrine porocarcinoma: K10 is strongly expressed in the intraepidermal tumor cells, reported by Kurokawa et al (100) (with permission) (original magnification, × 40).…”
Section: Distribution and Significance Of Keratin Expression In Humanmentioning
confidence: 82%
“…Eccrine spiradenoma: Spiradenoma exhibits a marker spectrum of keratins and α‐smooth muscle‐type actin similar to that of cylindroma (25,73,75–77), suggesting differentiation pathways of secretory, myoepithelial (Fig. 3f) (76) and ductal epithelial cells. One of these reports suggested that eccrine spiradenoma differentiates to the transitional portion between the secretory portion and coiled ducts of eccrine glands (77).…”
Section: Distribution and Significance Of Keratin Expression In Cutanmentioning
confidence: 98%